The effect of different polyphenols against neurotoxicity induced by quinolinic acid in U87-MG glial cells - Santos, Júlia Maiara dos (My University, 2021)
Neurodegenerative disorders (ND) are very debilitating aging-related diseases and mitochondrial dysfunction, oxidative stress and nitrosative stress (ONS) have been demonstrated to be associated with its clinical manifestations. Mitochondria stand out as crucial organelles in the interplay between neurodegeneration and neuroinflammation, and polyphenols are promising mitochondria-targeting medicine. Phenolic compounds can regulate mitochondria by means of controlling their redox state, function and apoptosis system. In this work, it was investigated the neuroprotective potential of Araucaria angustifolia (AAE) and Camellia sinensis (GT) extracts and six isolated compounds (resveratrol, gallic acid, ellagic acid, catechin, epicatechin and proanthocyanidins) in a neurodegeneration model using quinolinic acid (QA). U87-MG glial cells were pre-treated with AAE or GT or one of the phenolic compounds for 1 hour and then, exposed to QA for 24 hours. Cells exposed to QA presented decreased viability, exacerbated reactive oxygen species (ROS) generation, reduced the mitochondrial membrane potential, and increased inflammatory response. Despite the similar results found with both GT and AAE, the last one was capable to prevent all the parameters tested in this work. In conclusion, we suggest that AAE could be a potential agent to prevent ND related to mitochondrial dysfunction associated with ONS. [resumo fornecido pelo autor]
Doenças neurodegenerativas (DN) são desordens altamente debilitantes relacionadas ao envelhecimento, e a disfunção mitocondrial, estresse oxidativo e nitrosativo (EON) têm sido associados com as manifestações clínicas desse grupo de patologias. As mitocôndrias se destacam como organelas cruciais na relação entre a neurodegeneração e a neuroinflamação, e nesse sentido, os polifenóis são considerados promissores enquanto fármacos que têm como alvo as mitocôndrias. Compostos fenólicos são capazes de regular as mitocôndrias através do controle de seu estado redox, função e sistema apoptótico. Neste trabalho investigou-se o potencial neuroprotetor dos extratos de Araucaria angustifolia (AAE) e Camellia sinensis (GT), bem como de seis compostos isolados (resveratrol, ácido gálico, ácido elágico, catequina, epicatequina e proantocianidinas) em um modelo de neurodegeneração usando ácido quinolínico (AQ). Células gliais U87-MG foram pré-tratadas com AAE ou GT ou um dos compostos fenólicos por 1 hora e, então, expostas ao AQ por 24 horas. As células expostas ao AQ apresentaram diminuição da viabilidade, produção exacerbada de espécies reativas de oxigênio (EROs), redução do potencial de membrana mitocondrial e aumento da resposta inflamatória. Apesar dos resultados similares encontrados com o GT e o AAE, este último se destacou por ser capaz de prevenir todos os parâmetros testados neste trabalho. Em conclusão, sugere-se que o AAE apresenta-se como um agente em potencial para a prevenção de DN relacionadas com a disfunção mitocondrial associada ao EON. [resumo fornecido pelo autor]
Keywords: Sistema nervoso - Degeneração; Polifenóis; Estresse oxidativo; Ácido quinolínico